Bioinspired Microstructured Materials for Optical and Thermal Regulation. Issue 6 (19th July 2020) - Dou, Shuliang; Xu, Hongbo; Zhao, Jiupeng; Zhang, Ke; Li, Na; Lin, Yipeng; Pan, Lei; Li, Yao
Abstract: Precise optical and thermal regulatory systems are found in nature, specifically in the microstructures on organisms' surfaces. In fact, the interaction between light and matter through these microstructures is of great significance to the evolution and survival of organisms. Furthermore, the optical regulation by these biological microstructures is engineered owing to natural selection. Herein, the role that microstructures play in enhancing optical performance or creating new optical properties in nature is summarized, with a focus on the regulation mechanisms of the solar and infrared spectra emanating from the microstructures and their role in the field of thermal radiation. The causes of the unique optical phenomena are discussed, focusing on prevailing characteristics such as high absorption, high transmission, adjustable reflection, adjustable absorption, and dynamic infrared radiative design. On this basis, the comprehensive control performance of light and heat integrated by this bioinspired microstructure is introduced in detail and a solution strategy for the development of low‐energy, environmentally friendly, intelligent thermal control instruments is discussed. In order to develop such an instrument, a microstructural design foundation is provided. Abstract : Precise optical and thermal regulatory systems are found in nature, specifically in the microstructures on organisms' surfaces. The comprehensive control performance of light and heat integrated by these bioinspired microstructures is introduced and a solution strategy for the development of low‐energy, environmentally friendly, intelligent thermal control instruments is provided.